MEMAJUKAN UKM CONFETTI DENGAN MEMANFAATKAN TEKNOLOGI DIGITAL - Ardijan Handijono; Rudy Irawan Gunarto; Eka Kusuma Dewi; Samsul Marpitasa; Yunita Kwartarani (S1 Accounting Program, Universitas Pamulang, 2019)
Our PKM partners are a family company engaged in the manufacture of T-shirt sheets, which have the trademark